2017
DOI: 10.3390/agronomy7040077
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Sources and Rates Affect Soybean Seed Composition in Mississippi

Abstract: Soybean (Glycine max L.) seed is a major source of protein, oil, carbohydrates and other nutrients that are important for human and animal nutrition. Producers have considered applying nitrogen (N) fertilizer to soybean crop to maximize seed yield; however, its effect on seed composition is not well understood. The objective of this two-year (2015 and 2016) study was to evaluate the effects of N fertilizer sources and application rates (45, 90, 135 and 179 kg N ha −1 ) on soybean seed composition on two soil t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 44 publications
2
11
0
Order By: Relevance
“…It is possible that our second split-application of N fertilizer 2 weeks after R5 has contributed to increasing seed protein concentration, which partially explains the different results from the study by Gutiérrez-Boem et al (2004). Lastly, previous studies evaluating early N applications at planting and up to the R1 growth stage found no effect (Osborne and Riedell, 2006;Wilson et al, 2014) and even reductions (Ray et al, 2006;Kaur et al, 2017) in seed protein concentration. N fertilizer applications were found to decrease protein in irrigated trials in Mississippi (Ray et al, 2006;Kaur et al, 2017).…”
Section: Effect Of N Fertilizer Applications After R5mentioning
confidence: 65%
See 1 more Smart Citation
“…It is possible that our second split-application of N fertilizer 2 weeks after R5 has contributed to increasing seed protein concentration, which partially explains the different results from the study by Gutiérrez-Boem et al (2004). Lastly, previous studies evaluating early N applications at planting and up to the R1 growth stage found no effect (Osborne and Riedell, 2006;Wilson et al, 2014) and even reductions (Ray et al, 2006;Kaur et al, 2017) in seed protein concentration. N fertilizer applications were found to decrease protein in irrigated trials in Mississippi (Ray et al, 2006;Kaur et al, 2017).…”
Section: Effect Of N Fertilizer Applications After R5mentioning
confidence: 65%
“…Therefore, high rates of N accumulation in the seed must come from mining of inorganic N mineralized from soil organic matter, biological N fixation, or from remobilization of N from vegetative tissues to the seed. While the availability of N during the seed filling phase may be critical, most studies have evaluated the impact of early-season N fertilizer applications on seed protein concentration rather than late-season applications (Osborne and Riedell, 2006;Ray et al, 2006;Wilson et al, 2014;Kaur et al, 2017). A meta-analysis conducted in 2009 found an average increase in protein concentration of +0.7% with N fertilization before flowering, and of +1.1% with applications during flowering and pod setting relative to the unfertilized control (Rotundo and Westgate, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Current soybean grain pricing is based on yield and grain grading quality, which does not include seed oil or protein levels, or amino acid composition. Conversely, seed protein concentration is a factor for small grain prices, such as for wheat ( Triticum aestivum L.; Kaur et al., 2017; Weidenbenner et al., 2014). Many wheat producers receive grain price deductions if they do not meet protein requirements.…”
Section: Introductionmentioning
confidence: 99%
“…Taylor et al (2005) found that N applied to late-planted soybean in the Deep South, Alabama had no impact either on seed yield and quality or on protein and oil contents. Meanwhile, Kaur et al (2017) reported that N application at 179 kg ha À1 on clay soil reduced seed protein by 1.05% compared to unfertilised soybeans, however, it increased oil content by 0.7%. Soybean seed composition showed inconsistent responses to N fertilisation, probably due to climatic conditions, such as lower temperatures and higher precipitation during seed filling may reduce protein and oil concentration, whereas high air temperatures and moderate rainfall at the seed filling period can result in higher protein concentration in soybean seeds (Bennett and Krishman, 2005).…”
Section: Protein and Lipid Content (%)mentioning
confidence: 99%